Gentiacaulein inhibits glucose transport to induce PRKAA1-mediated autophagy to clear amyloid beta and associated inflammation in primary astrocytes - Ankita Sharma; Sukhleen Kaur; Abubakar Wani; Dilpreet Kour; Mehboob Ali; Syed Mudassir Ali; Lakhvinder Singh; Abhishek Gour; Utpal Nandi; Manish Datt; Parduman Raj Sharma; Conrad C Weihl; et al. (Autophagy Reports)
Being present in substantial numbers, astrocytes play an indispensable role in maintaining homeostasis in the brain. However, their positive or negative involvement in pathological conditions in the brain has not been explored much. In recent years, an emerging thought of targeting astrocytes for the resolution of neurodegenerative diseases has gained momentum. In this study, we have attempted to explore the likelihood of targeting astrocytes by using a natural compound, gentiacaulein (GENT), for clearance of amyloid-β (Aβ) through autophagy and amelioration of neuroinflammation associated with Aβ. We found that GENT treatment of astrocytes hampered the transport of glucose across the cell membrane, which resulted in a reduction in ATP production. With increased treatment time, AMP: ATP ratio was increased significantly, which caused the induction of PRKAA1-mediated autophagy. We further show that increased autophagy considerably enhanced the clearance of amyloid-β by astrocytes. GENT reduced the Aβ mediated inflammation by inhibiting the nuclear translocation of NF-κB and decreased the release of inflammatory cytokines TNF-α and IL-6. The role of PRKAA1 in GENT-induced autophagy and anti-inflammatory activity was confirmed when its knockdown reversed these effects. Our data suggest that targeting astrocytes can be a good strategy to prevent/treat Alzheimer’s disease.